The Correlation of Ergonomic Risk Factor with Musculoskeletal Complaints in Batik Workers - Galuh Sistha Prabarukmi; Noeroel Widajati (Universitas Airlangga, 2020)
Introduction: Batik is one of Indonesia’s cultural wealth which was established as an intangible cultural heritage by UNESCO in 2009. Batik fabrics have been actively produced in both micro and macro industries in Indonesia. The process of batik production still faithfully employs manual labor. The large number of workers involved in batik production activities causes them to potentially suffer from occupational diseases such as musculoskeletal disorders. Various factors can cause workers to suffer from musculoskeletal complaints, one of them is ergonomic factor. Batik Madura home industry is one of the largest batik-producing home industries in Bangkalan District, Madura. This study object was to determine the correlation between ergonomic risk factors and musculoskeletal complaints in workers of Batik Madura home industry. Methods: This was an observational study through cross sectional design. Data collection was conducted through observation and interviews with the workers of Batik Madura home industry. The population in this study was 61 workers of Batik Madura home industry. This study used total sampling technique in which the whole population were taken as the sample. Results: There was a very strong correlation of ergonomic chance factor with musculoskeletal complaints (r=0.876) on workers of Batik Madura home industry. Conclusion: There was a very strong correlation of ergonomic chance factor with musculoskeletal complaints (r=0.876) on workers of Batik Madura home industry.Keywords: ergonomic risk factor, musculoskeletal complaints, batik workers